Nanocatalysts in Environmental Applications - Bagheri, Samira (Green Energy and Technology,, 2018)
This book presents a range of nanocatalysts, together with their primary environmental applications and use in chemical production processes. In addition, it describes the nanomaterials used for catalysts and details their performance. The book introduces readers to the fundamentals and applications of nanocatalysis, synthesis, characterization, modification and application. Further topics include: landfill organic pollutant photodegradation; magnetic photocatalysis; synergistic effects on hydrogenated TiO2; and photoinduced fusion of gold-semiconductor nanoparticles. A detailed explanation of the chemistry of nanostructures and the ability to control materials at the nano-scale rounds out the coverage. Given the central importance of research in nanotechnology and nanoscience for the development of new catalysts, the book offers a valuable source of information for researchers and academics alike. It will also benefit industrial engineers and production managers who wish to understand the environmental impact of nanocatalysts.